Sedimentology and Stratigraphy of the Early Neogene Sarawak Basin (Tatau-Bintulu Road), Sarawak, Malaysia - Ngui, Jia Qi (Universiti Teknologi PETRONAS, 2016)
Sarawak is a state that has been divided into four zones, namely the West Borneo Basement, Kuching Zone, Sibu Zone and Miri Zone. The Sarawak Basin in the state covers both onshore and offshore areas, divided into several geological provinces which include West Baram Delta, Balingian, Central Luconia, West Luconia, Southwest Luconia, Tinjar, Tatau and Southwest Sarawak Provinces. Provinces in the basin are of Palaeogene to recent age. On the shelf of the basin, sedimentary succession exceeds 12 km thick (Denis & Lamy, 1990). The study area which is located between Tatau and Bintulu, consists of sediments which are Neogene in age. Sedimentology and stratigraphy study was carried out on the Neogene sedimentary succession at the study area, which stretches around 10 km to 15 km northeast of Tatau town and southwest of Bintulu town. A total of four outcrops were studied. The results are based on field survey of the outcrops across the study area and laboratory analysis of the collected sedimentary samples from the field. Sedimentary succession across the field is described and recorded through sedimentary logging. Composition of the sedimentary samples is analyzed through petrography analysis. Grain size analysis is carried out to determine the classification of the sediments. Architecture and distribution of the minerals are analyzed through SEM analysis and the elemental compositions of individual particles are determined through EDX analysis. As the study area consist of shallow marine deposits, fossils and trace fossils can be found at the outcrops with varying bioturbation index. The evidences gathered demonstrate the deposition and basin fill of the Neogene Sarawak Basin, showing the build-up stratigraphy of the sedimentary succession. Depositional environment of the study area can be deduced from the sedimentary and stratigraphy study.